Cat burglar black - Sala, Richard (First Second, 2009)
K.'s aunt, who works at the Bellsong Academy for Girls, has invited K. to attend the school. But as soon as she arrives, K. notices some strange goings-on: her aunt has suddenly taken ill; there are only three other students and no regular classes; and a statue speaks to K. when no one else is around.